2018
DOI: 10.1039/c8cc01400k
|View full text |Cite
|
Sign up to set email alerts
|

High-yielding18F radiosynthesis of a novel oxytocin receptor tracer, a probe for nose-to-brain oxytocin uptakein vivo

Abstract: Probing the mechanism of intranasal oxytocin brain uptake through generation and validation of a novel peptide PET tracer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Research in rodents and monkeys has shown that molecules administered intranasally can be transported to the olfactory bulb within a time-frame of 45-90 min 54,55 , and possibly much faster [56][57][58] . A recent comparison of intranasal and intravenous administration of a new OT receptor tracer in mice supported this hypothesis by showing uptake of the intranasally administered tracer to the olfactory bulb, while increases in this area after the intravenous administration of the tracer were almost negligible 59 . The increases of the concentration of the tracer in the olfactory bulb following its intranasal administration could be observed as soon as 30 min post-dosing, which fits the time-frame of the effects we report in our study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Research in rodents and monkeys has shown that molecules administered intranasally can be transported to the olfactory bulb within a time-frame of 45-90 min 54,55 , and possibly much faster [56][57][58] . A recent comparison of intranasal and intravenous administration of a new OT receptor tracer in mice supported this hypothesis by showing uptake of the intranasally administered tracer to the olfactory bulb, while increases in this area after the intravenous administration of the tracer were almost negligible 59 . The increases of the concentration of the tracer in the olfactory bulb following its intranasal administration could be observed as soon as 30 min post-dosing, which fits the time-frame of the effects we report in our study.…”
Section: Discussionmentioning
confidence: 89%
“…The second mechanism postulates that OT reaches the cerebrospinal fluid (CSF) and brain parenchyma via passive diffusion through perineural clefts in the nasal epithelium, which provide a gap in the blood-brain barrier 17 . While some animal work is consistent with the existence of the second mechanism 18 , there is a lack of robust evidence to support the existence of noseto-brain transport in humans 15,19 .…”
mentioning
confidence: 99%
“…Research in rodents and monkeys has shown that molecules administered intranasally can be transported to the olfactory bulb within a time-frame of 45-90 min (61, 62), and possibly much faster (63). A recent comparison of intranasal and infusion administration of a new OT receptor tracer in mice supported this hypothesis by showing uptake of the intranasally administered tracer to the olfactory bulb, while increases in this area after the infusion of the tracer were almost negligible (64). The increases of the concentration of the tracer in the olfactory bulb following its intranasal administration could be observed as soon as 30 minutes post-dosing, which fits the time-frame of the effects we report in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism postulates that the peptide reaches the cerebrospinal fluid (CSF) and brain parenchyma via passive diffusion through perineural clefts in the nasal epithelium, which provide a gap in the blood-brain barrier (19). While some animal work is consistent with the existence of the second mechanism (20), there is a lack of robust evidence to support the existence of nose-tobrain transport in humans (17,21).…”
mentioning
confidence: 99%
“…A recent study in mice reported naked plasmid delivery by the intranasal route resulted in significantly elevated levels of plasmid in the olfactory nerves and hypothalamus compared to all other brain regions whose concentrations did not differ from the control region, the cerebellum (Oviedo, et al, 2017). A recently developed radioligand for the oxytocin receptor, when administered intranasally, resulted in enhanced binding in the olfactory bulbs suggesting a direct nose to brain transport via the intranasal route (Beard, et al, 2018). It remains to be determined though, whether the intranasal route leads to improved penetrance of brain parenchyma overall.…”
Section: Enhancement Of Endogenous Cns Peptide Signalingmentioning
confidence: 99%